The response to growth hormone treatment in prepubertal children with growth hormone deficiency in Japan: Comparing three consecutive years of treatment data of The Foundation for Growth Science in Japan between the 1990s and 2000s - Tanaka, Toshiaki; Hasegawa, Tomonobu; Yokoya, Susumu; Isojima, Tsuyoshi (Endocrine Journal, 2017)
Growth hormone (GH) treatment for children with GH deficiency (GHD) is effective in improving adult height. To achieve favorable effects, GH treatment before puberty is very important, because prepubertal height gain is highly correlated with total height gain. However, no report has studied the effects by analyzing a nationwide data from recent GHD patients in Japan. We investigated the response to GH treatment using data compiled in the Foundation for Growth Science in Japan, and compared the effects between the 1990s and 2000s using analysis of covariance. We analyzed 534 prepubertal GHD subjects treated in the 2000s with three consecutive years of data from the start and investigated predictive factors for the effects. The cumulative height standard deviation score (SDS) change over three years of GH treatment was 0.91 ± 0.57 and 1.20 ± 0.62 in the 1990s and 2000s, respectively. Subjects in the 2000s were divided into three groups by severity, and the cumulative height SDS was 1.60 ± 0.93, 1.20 ± 0.54, and 1.00 ± 0.40 indicating severe, moderate, and mild GHD, respectively. Age and height SDS at the start and severity were identified as independent predictive factors. We also found a significant difference in the effects between the two cohorts after adjusting for the different factors (regression coefficient: -0.069, 95% confidence interval: -0.11 to -0.030, p = 0.0006), which might be due to the GH dose effect. We conclude that the effects of GH treatment in the 2000s had improved compared with those in the 1990s.